A large scale prospective clinical and psychometric validation of the EORTC colorectal (QLQ-CR29) module in Polish patients with colorectal cancer - Sanna, B; Bereza, K; Paradowska, D; Kucharska, E; Tomaszewska, I M; Dudkiewicz, Z; Golec, J; Bottomley, A; Tomaszewski, K A (European journal of cancer care, 2017)
The purpose of our study was to assess if the Polish translation of the European Organisation for Research and Treatment of Cancer (EORTC) Colorectal Cancer (CRC)-Specific Quality of Life Questionnaire (QLQ-CR29) is an acceptable and psychometrically valid measure to collect quality of life (QoL) data in Polish patients with CRC for use in clinical trials and clinical practice. A total of 150 patients undergoing treatment for CRC were prospectively enrolled in the study. Psychometric assessment of the translated QLQ-CR29 structure, reliability, convergent and divergent validity, and clinical validity was subsequently performed. The Cronbach's alpha coefficient ranged from 0.70-0.89, indicating acceptable internal consistency. For test-retest reliability, the ICCs for each item ranged from 0.59-0.91, with exceptions for urinary incontinence and dysuria, indicating good to excellent reproducibility. In multi-trait scaling analyses, the criterion for item convergent and divergent validity was satisfied. The correlations between the EORTC QLQ-CR29 and QLQ-C30 scales were mostly low (r < .40), with a few items demonstrating higher correlations. The known group comparisons analyses demonstrated the ability of the questionnaire to distinguish between patients' differing age, stoma status, and treatment intent. The Polish translation of the QLQ-CR29 is a psychometrically reliable and valid tool. The results of this study are congruent with that of EORTC validation.
Keywords: senioři; Poland; Psychometrics; Reproducibility of Results; questionnaire; Body Image; colorectal cancer; kolostomie; senioři nad 80 let; psychometrie; Colostomy; reprodukovatelnost výsledků; kolorektální nádory; Middle Aged; průzkumy a dotazníky; Colorectal Neoplasms; mužské pohlaví; symptomy dolních močových cest; Prospective Studies; Adult; chirurgické stomie; Polsko; kvalita života; Lower Urinary Tract Symptoms; překlady; fekální inkontinence; Surgical Stomas; Aged, 80 and over; ženské pohlaví; Humans; prospektivní studie; Translations; inkontinence moči; Surveys and Questionnaires; pilotní projekty; lidé středního věku; Health Status; Pilot Projects; představa o vlastním těle; Urinary Incontinence; Fecal Incontinence; dospělí; zdravotní stav; Female; Aged; Quality of Life; quality of life; lidé; Male